2008
DOI: 10.1211/jpp.60.3.0005
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to S100 proteins have anxiolytic-like activity at ultra-low doses in the adult rat

Abstract: S100 proteins are small calcium-binding proteins interacting with numerous intra- and extra cellular targets involved in diverse physiological functions. In particular, S100 proteins may be involved in the regulation of anxiety-related behaviour. In the present study, the effects of affinity-purified antibodies to S100 proteins administered orally at ultra-low doses were evaluated in pre-clinical tests for anxiolytic-like activity in the adult rat. In the Vogel conflict test in the rat, antibodies to S100 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
2
14
0
1
Order By: Relevance
“…Increased sucrose consumption after antibody treatment can also be due to disorders in learning of passive avoidance of electric current by animals of both strains, though this behavioral reaction was more pronounced (drinking suppression during CS) and more generalized (reaction to DS) in GC compared to Wistar rats. This disturbed avoidance under the effect of antibodies to S-100B is in good agreement with their anxiolytic effect [8].…”
Section: Resultssupporting
confidence: 77%
“…Increased sucrose consumption after antibody treatment can also be due to disorders in learning of passive avoidance of electric current by animals of both strains, though this behavioral reaction was more pronounced (drinking suppression during CS) and more generalized (reaction to DS) in GC compared to Wistar rats. This disturbed avoidance under the effect of antibodies to S-100B is in good agreement with their anxiolytic effect [8].…”
Section: Resultssupporting
confidence: 77%
“…Published data suggest that low doses of AТ-S100 can produce anxiolytic and antidepressant effects in experimentally designed confl ict situations in rats [4]. Recent papers confi rm these data [6,10]; antihypoxic (survival under hypoxic conditions) and differentiating (neuritogenic) effects of LAТ-S100 were revealed in neuroblastoma С-1300 culture [5]. As an extension of these studies we attempted to modulate some behavioral changes observed during LTS with antibodies to S100B for elucidation of the mechanism of the possible protective effect.…”
Section: Resultsmentioning
confidence: 90%
“…Another modifi cation of Vogel confl ict test was developed and validated in the laboratory Porsolt & Partners Pharmacology (France) [7]. The experiments were performed on male Rj:Wistar (Han) rats (n=100, 160-227 g) housed 5 animals per cage, as in the previous experiment.…”
Section: Methodsmentioning
confidence: 99%